2018
DOI: 10.4097/kjae.2018.71.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between lignocaine nebulization and airway nerve block for awake fiberoptic bronchoscopy-guided nasotracheal intubation: a single-blind randomized prospective study

Abstract: BackgroundThe preferred management strategy for difficult airways is awake fiberoptic bronchoscopy-guided intubation, which requires effective airway anesthesia to ensure patient comfort and acceptance. This randomized single-blind prospective study was conducted to compare lignocaine nebulization and airway nerve block for airway anesthesia prior to awake fiberoptic bronchoscopy-guided intubation.MethodsSixty adult patients scheduled for surgical procedures under general anesthesia were randomly allocated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 16 publications
4
33
0
Order By: Relevance
“…One recent similar study concluded that airway anesthesia using airway nerve blocks is superior to lignocaine nebulization for awake fiberoptic bronchoscopy-guided nasotracheal intubation, in terms of ease of intubation, less intubation time and patient comfort and satisfaction. But in that study authors used jet nebulization and blind airway nerve block whereas in present study ultrasonic nebulisation and ultrasound guided nerve block was used 11 .…”
Section: Discussionmentioning
confidence: 89%
“…One recent similar study concluded that airway anesthesia using airway nerve blocks is superior to lignocaine nebulization for awake fiberoptic bronchoscopy-guided nasotracheal intubation, in terms of ease of intubation, less intubation time and patient comfort and satisfaction. But in that study authors used jet nebulization and blind airway nerve block whereas in present study ultrasonic nebulisation and ultrasound guided nerve block was used 11 .…”
Section: Discussionmentioning
confidence: 89%
“…Based on a previous study by Mathur et al [18] who reported 30% difference in the intubation time, a total sample size of 50 patients (25 patients in each group) enables us to reject the null hypothesis that the failure rates for study and control subjects are equal with probability (power) of 0.80, when type I error probability associated with this test is 0.05, after adding 20% for possible dropout of patients.…”
Section: Sample Sizementioning
confidence: 99%
“…It would be safe and not unpleasant for the patient and would at the same time provide acceptable conditions for the bronchoscopist. (Mathur et al, 2018) Hence, this study aims to compare local anesthetic application techniques, i.e., airway nerve blocks and "Spray as you go" technique for patients undergoing awake beroptic intubation.…”
Section: Introductionmentioning
confidence: 99%